The Role of Teachers in Handling Students’ Bullying Behavior at Sokong 2 State Elementary School - Yodi Aprianto; Raden Sumiadi; Nunung Mardianti (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
The role of teachers in dealing with bullying behavior of students in SDN 2 Sokong. The purpose of the study was to describe the role of teachers ' efforts in dealing with bullying behavior of students. This study is a type of qualitative research with a case study approach to review further related to the handling of teachers in forming positive behavior in students. This study was conducted in Sokong village with the consideration that Sokong village as a reference implementation in the handling of negative behavior of students. In this study the main instrument is the researcher himself and is supported by interviews, documentation and observation instruments. The results showed that the teachers in SDN 2 Sokong are very enthusiastic in dealing with bullying behavior in students, and ahlak ethics and manners have a psitive impact on the cultivation of the values of the character of the students themselves so that there is never a behavior that reflects bullying behavior that can interfere with the child's psychomotor development. The form of bullying siawa is bullying verball and non verball where the impact of bullying that occurs is psychological and physical then the bullying behavior factors are from family, peers, mass media and individuals from themselves.